2009
DOI: 10.1103/physrevb.79.035206
|View full text |Cite
|
Sign up to set email alerts
|

Negative donors in bulk Si andSi/SiO2quantum wells in a magnetic field

Abstract: The spin-singlet ground states of a D − ion in bulk Si and Si/ SiO 2 quantum wells have been investigated in the presence of a magnetic field, using a diffusion quantum Monte Carlo method. By neglecting the central-cell correction, the negative donor state can be assigned by the valley indexes of two trapped electrons. In the bulk Si, the ground-state energies of negative donors of both the intervalley and intravalley configurations split into two levels in a magnetic field along the z axis and the lowest-ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For Si, we obtained ⑀ ij = 1.82 meV and ⑀ ii = 1.57 meV in good agreement with 1.75 meV and 1.55 meV for an interstitial Li impurity. 23 In a preceding paper, 29 we studied negative donors in Si/ SiO 2 quantum wells in a presence of the magnetic field without the valley-orbit interaction and found that strong confinement effect was induced by both the well and the magnetic field.…”
Section: Introductionmentioning
confidence: 98%
“…For Si, we obtained ⑀ ij = 1.82 meV and ⑀ ii = 1.57 meV in good agreement with 1.75 meV and 1.55 meV for an interstitial Li impurity. 23 In a preceding paper, 29 we studied negative donors in Si/ SiO 2 quantum wells in a presence of the magnetic field without the valley-orbit interaction and found that strong confinement effect was induced by both the well and the magnetic field.…”
Section: Introductionmentioning
confidence: 98%
“…An electric gate or an external magnetic field can be used to control and manipulate the electronic states to realize the operation of the devices. The ground state of a donor localized near a semiconductor/insulator/metal interface was recently investigated by using the finite element technique [9,10], the variational approach [2,9] and the quantum Monte Carlo simulation [11]. The effects of the gate potential, the screening of the metallic gate, the finite thickness of the insulator layer between the semiconductor and the gate, as well as the image charge on the impurity potential and the donor states, were investigated [9,10].…”
Section: Introductionmentioning
confidence: 99%